Seychelles : Assessment Letter for the International Community. (Policy Papers; Policy Paper, 2009)
This letter provides an assessment of recent macroeconomic developments in Seychelles and an update on the discussions of Fund staff with the Seychelles authorities on macroeconomic policies and structural reforms that could form the basis for the authorities' request for a new arrangement supported by the International Monetary Fund.